Hариси з палеолінгвістичної характеристики італійської групи мов - Храбскова, Д.М. (Культура народов Причерноморья, 2013)
Соціальна спрямованість сучасних лінгвістичних досліджень надає актуальності
впровадженню нових вимірів у розвідки, присвячені класичним мовам. Стає зрозумілим, що
соціолінгвістична методика наукових пошуків може висвітлити в інакшому ракурсі загальновідомі
факти із історії давніх мов, які здатні вплинути на процеси мовної реконструкції і накреслити основні
вектори лінгвокультурних ізоглос європейського континенту. Саме такі практичні цілі постають перед
палеолінгвістичним напрямом, що є цариною новітніх філологічних студій. Наукова новизна праць,
виконаних у руслі палеолінгвістики, полягає, у першу чергу, в залученні польових методів збору і
міждисциплінарних засобів класифікації та інтерпретації отриманого матеріалу до вивчення і
відновлення мертвих мов, що їхні писемні пам'ятки більшою частиною є зруйнованими. Теоретична
занчущість властива кожному дослідженню, що проводиться у межах зазначеного напряму, оскільки
термінологічна база палеолінгвістики знаходиться у стадії формування, а методологія не є
кодифікованою. Мета наведеної праці полягає у встановленні спільних і розбіжних рис між мовами
італійської групи через вивчення конкретних історичних писемних пам'яток та семантики
рудиментарної лексичної спадщини.
Ключові слова: палеографія, палеолінгвістичні параметри, індоєвропейська прамова, італійські мови. Социальная направленность современных лингвистических исследований придает
актуальности процессу внедрения новых измерений в исследования, посвященные классическим языкам.
Становится очевидным, что социолингвистическая методика научных изысканий способна
представить в совершенно ином ракурсе общеизвестные факты из истории древних языков, которые, в
свою очередь, могут повлиять на направление и темпы процессов языковой реконструкции и обозначить
основные векторы лингвокультурных изоглосс европейского континента. Именно такие практические
цели ставятся перед палеолингвистическим направлением, которое формирует область новейших
филологических исследований. Научная новизна работ, выполненных в русле палеолингвистики
заключается в привлечении полевых методов сбора, междисциплинарных средств классификации, а
также интерпретации полученного языкового материала для изучения и восстановления мертвых
языков, письменные памятники которых большей частью утрачены. Теоретическое значение присуще
каждому исследованию, проводимому в пределах указанного направления, поскольку терминологическая
база палеолингвистики находится в стадии формирования, а ее методология – не кодифицирована. Цель
представленной работы заключается в установлении общих и отличительных черт между языками
италийской группы путем изучения конкретных исторических письменных памятников и семантики
рудиментарного лексического наследия.
Ключевые слова: палеография, палеолингвистические параметры, индоевропейский праязык,
италийские языки. The social orientation of contemporary linguistic research adds to the relevance of the introduction
of new measurements in the studies of classical languages. It becomes apparent that the sociolinguistic
methodology of scientific research is able to provide a completely different perspective on the well-known facts
about the history of the ancient languages, which, in turn, can influence the direction and pace of linguistic
reconstruction processes and highlight the main vectors of Linguocultural isoglosses of the European continent.
It is these practical goals set before paleolinguistical direction that form the emerging field of modern
philological research. The Scientific novelty of the work performed in the line of paleolinguistics consists of
using field collection methods, interdisciplinary classification tools, as well as the interpretation of the language
material for the study and restoration of the dead languages written monuments of which are mostly lost. The
theoretical value is inherent in every study conducted within the specified direction since the terminological base
of paleolinguistic is in the formative stage, and its methodology is not codified. The purpose of the present work
is to establish common and distinctive features of the languages of Italic group by examining specific historical
written monuments and the semantics of rudimentary lexical heritage. The Summary of findings for the study
allows to conclude that the gradual process of interbreeding of communicative formations of the Italic languages
continuum leads to the fact that ethno-linguistic map of Italy in the middle of the I millennium BC, was largely
heterogeneous; despite this fact, it is possible to determine, with sufficient precision and reliability, the areas of
compact settlement of tribes and peoples, whose languages and dialects in the period up to the II century BC,
had a gradual effect on the formation and development of the Latin language and its literary tradition.
Keywords: paleography, paleolinguistical parameters, Indo-European proto-language, the Italic languages
group.